Written Essays and research competence. The case of the Hellenic Open University’s Degree Master Teaching French as Foreign/International Language - Marina Vihou; Suzana Avramidou; Anastasia Kaffe; Sofia Ourolidou (9 th International Conference in Open & Distance Learning - November 2017, Athens, Greece, 2017)
The development of the students’ research competence in a Distance Postgraduate Program is the main question of our report. Its investigation was attempted through the study of the postgraduate students’ representations in the Module French as Foreign/International Language Program of Hellenic Open University. Particularly, the questionnaire sent to the students of this Program, focused on the role of Written Essays carried out during it, in terms of the development of students’ research competence.